Design of Diketopyrrolopyrrole (DPP)‐Based Small Molecules for Organic‐Solar‐Cell Applications. Issue 2 (9th November 2016) - Tang, Ailing; Zhan, Chuanlang; Yao, Jiannian; Zhou, Erjun
Abstract : After the first report in 2008, diketopyrrolopyrrole (DPP)‐based small‐molecule photovoltaic materials have been intensively explored. The power conversion efficiencies (PCEs) for the DPP‐based small‐molecule donors have been improved up to 8%. Furthermore, through judicious structure modification, DPP‐based small molecules can also be converted into electron‐acceptor materials, and, recently, some exciting progress has been achieved. The development of DPP‐based photovoltaic small molecules is summarized here, and the photovoltaic performance is discussed in relation to structural modifications, such as the variations of donor–acceptor building blocks, alkyl substitutions, and the type of conjugated bridges, as well as end‐capped groups. It is expected that the discussion will provide a guideline in the exploration of novel and promising DPP‐containing photovoltaic small molecules. Abstract : Diketopyrrolopyrrole (DPP)‐based small‐molecule photovoltaic materials are being intensively explored and can be divided into three types: single‐DPP, double‐DPP, and multi‐DPP respectively. The recent progress regarding DPP‐based photovoltaic small molecules is highlighted and the photovoltaic performance in relation to structural modification such as the variations of donor–acceptor building blocks, alkyl substitutions, the type of conjugated bridges, and the type of end‐capped groups is discussed.